The use of dendrochronological methods in environmental monitoring of Kyrgyzstan (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article discusses the possibilities of dendrochronology in solving environmental problems and forestry research. The use of the dendrochronological method for assessing climate change and anthropogenic impact on forest ecosystems is presented. The prospects for the development of this scientific direction in the territory of Kyrgyzstan are considered.
Keywords: environmental monitoring, dendrochronology, natural processes, model trees, climate